Construction of Dye Sensitized Solar Cell with an Ethanol Based Anthocyanin Extraction of Grape Skin as Its Light Absorbing Material. Issue 1 (November 2020) - See, S C; Mercado, M M; Corpuz, J Z; Balbin, J; Chua, E
Abstract: As the use of renewable energy resources such as solar energy still leads to the augmentation of energy supply insufficiency, this study aimed to provide an alternative source of economical, time-efficient and environment-friendly solar cell as a powerful potential energy source using grape skin Dye-Sensitized Solar Cell. The experimental parameter was the concentration of anthocyanin. The anthocyanin was extracted by boiling the dried grape skin in the ethanol solution. The semiconductor paste was prepared by mixing Titanium Dioxide and very dilute Acetic Acid (0.1 mL acetic acid in 50 mL water), and was coated on the conductive side of the conductive glass through screen printing method. The Construction of DSSC was done layer by layer. It consisted of working electrode (TiO2 semiconductor-dye) and counter electrode with carbon applied on it. The construction time for the 5 dye-sensitized solar cells was approximately less than an hour. The measured voltages were 0.43V, 0.40V, 0.40V, 0.45V, and 0.41V respectively, while the measured short-circuit currents were: 41µA, 38µA, 35µA, 41µA, and 39µA respectively.